Murine Langerin(+) dermal dendritic cells prime CD8(+) T cells while Langerhans cells induce cross-tolerance - Flacher, Vincent (Blackwell Publishing Ltd, 2014)
Skin dendritic cells (DCs) control the immunogenicity of cutaneously administered vaccines. Antigens targeted to DCs via the C-type lectin Langerin/CD207 are cross-presented to CD8(+) T cells in vivo. We investigated the relative roles of Langerhans cells (LCs) and Langerin(+) dermal DCs (dDCs) in different vaccination settings. Poly(I:C) and anti-CD40 agonist antibody promoted cytotoxic responses upon intradermal immunization with ovalbumin (OVA)-coupled anti-Langerin antibodies (Langerin/OVA). This correlated with CD70 upregulation in Langerin(+) dDCs, but not LCs. In chimeric mice where Langerin targeting was restricted to dDCs, CD8(+) T-cell memory was enhanced. Conversely, providing Langerin/OVA exclusively to LCs failed to prime cytotoxicity, despite initial antigen cross-presentation to CD8(+) T cells. Langerin/OVA combined with imiquimod could not prime CD8(+) T cells and resulted in poor cytotoxicity in subsequent responses. This tolerance induction required targeting and maturation of LCs. Altogether, Langerin(+) dDCs prime long-lasting cytotoxic responses, while cross-presentation by LCs negatively influences CD8(+) T-cell priming. Moreover, this highlights that DCs exposed to TLR agonists can still induce tolerance and supports the existence of qualitatively different DC maturation programs.